2007
DOI: 10.1053/j.gastro.2007.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Effector Role of Neonatal Hepatic CD8+ Lymphocytes in Epithelial Injury and Autoimmunity in Experimental Biliary Atresia

Abstract: Background and Aims-Lymphocytes populate the livers of infants with biliary atresia, but it is unknown whether neonatal lymphocytes regulate pathogenesis of disease. Here, we investigate this question by examining the role of T lymphocytes in the destruction of extrahepatic bile ducts of neonatal mice using an experimental model of biliary atresia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
141
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(151 citation statements)
references
References 26 publications
8
141
1
1
Order By: Relevance
“…[1][2][3], recent analyses of livers and/or biliary remnants at diagnosis uncovered a prominent proinflammatory footprint and an enriched population of CD4 + CD8 + lymphocytes, with evidence of an oligoclonal expansion to as-yet-unidentified antigens (4-7). More direct support for the relevance of these findings to the pathogenesis of disease was obtained by mechanistic experiments in a neonatal mouse model of rhesus rotavirus-induced (RRVinduced) biliary atresia, in which the loss of Ifnγ and CD8 + lymphocytes prevented obstruction of bile ducts and suppressed the disease phenotype (8,9). Further, when virus-primed T cells were transferred to RRV-naive recipients, they homed to bile ducts and induced cholangitis (9,10).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…[1][2][3], recent analyses of livers and/or biliary remnants at diagnosis uncovered a prominent proinflammatory footprint and an enriched population of CD4 + CD8 + lymphocytes, with evidence of an oligoclonal expansion to as-yet-unidentified antigens (4-7). More direct support for the relevance of these findings to the pathogenesis of disease was obtained by mechanistic experiments in a neonatal mouse model of rhesus rotavirus-induced (RRVinduced) biliary atresia, in which the loss of Ifnγ and CD8 + lymphocytes prevented obstruction of bile ducts and suppressed the disease phenotype (8,9). Further, when virus-primed T cells were transferred to RRV-naive recipients, they homed to bile ducts and induced cholangitis (9,10).…”
Section: Introductionmentioning
confidence: 91%
“…More direct support for the relevance of these findings to the pathogenesis of disease was obtained by mechanistic experiments in a neonatal mouse model of rhesus rotavirus-induced (RRVinduced) biliary atresia, in which the loss of Ifnγ and CD8 + lymphocytes prevented obstruction of bile ducts and suppressed the disease phenotype (8,9). Further, when virus-primed T cells were transferred to RRV-naive recipients, they homed to bile ducts and induced cholangitis (9,10). These studies identified molecular and cellular effectors that regulate inflammation and obstruction of bile ducts, but the mechanisms by which the neonatal immune system initiates the injury to the duct epithelium remain undefined.…”
Section: Introductionmentioning
confidence: 94%
“…6 A similar T helper 1 response is replicated in the most promising animal model of BA, the rhesus rotavirus-infected newborn mouse model. [7][8][9] The innate immune response is also activated in the human BA liver, as demonstrated by the later appearance of cells of the CD68ϩ macrophage/ monocyte family in portal tracts and evidence of chemokine and cytokine release by these and related cells. 7 Abnormal expression of cellular adhesion molecules (intercellular cell adhesion molecule, CD54, vascular cell adhesion molecule, CD62E) on biliary epithelium and vascular endothelium and elevated circulating levels of soluble adhesion molecules have also been observed.…”
mentioning
confidence: 99%
“…This hyper-response is temporally restricted to the early neonatal period and functionally linked to a lower T-cell number (15). Even if lower in number, neonatal T cells can activate a broad pro-inflammatory program in response to tissue infection, as demonstrated by the effective clearance of RRV from the liver and biliary tract by neonatal CD8+ cells (16). A prominent pro-inflammatory footprint and an enriched population of CD4+ and CD8+ lymphocytes have been reported in the murine model, with evidence of an antigenic oligoclonal expansion (17)(18)(19)(20).…”
Section: Environmental Triggersmentioning
confidence: 99%
“…The loss of interferon-gamma (IFN-γ) or CD8+ lymphocytes prevents obstruction of bile ducts, suppressing the disease phenotype, and, when virus-primed T cells are transferred to RRV-naive recipients, they home to bile ducts and induce cholangitis. While clearing the virus, however, CD8+ cells can secondarily injure the epithelium and produce the obstructive phenotype typical of experimental BA (16).…”
Section: Environmental Triggersmentioning
confidence: 99%